2020
DOI: 10.1029/2020wr027603
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Channel Systems of a Low‐Relief, Low‐Gradient Floodplain: Comparison of Automatic Extraction Methods

Abstract: Intermittent floodplain channels are low-relief conduits etched into the floodplain surface and remain dry much of the year. These channels comprise expansive systems and are important because during low-level inundation they facilitate lateral hydraulic connectivity throughout the floodplain. Nevertheless, few studies have focused on these floodplain channels due to uncertainty in how to identify and characterize these systems in digital elevation models (DEMs). In particular, their automatic extraction from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 55 publications
0
19
0
Order By: Relevance
“…A DEM with 1 m resolution was generated from a 2010 lidar point cloud (South Carolina Department of Natural Resources) (Figure 1b). The lidar point cloud was reclassified to reduce misclassifications in ground returns, especially along floodplain channels (Xu et al., 2020). We then analyze the floodplain topography, through‐bank channel (TBC) profiles, and extract levees by a novel automatic approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A DEM with 1 m resolution was generated from a 2010 lidar point cloud (South Carolina Department of Natural Resources) (Figure 1b). The lidar point cloud was reclassified to reduce misclassifications in ground returns, especially along floodplain channels (Xu et al., 2020). We then analyze the floodplain topography, through‐bank channel (TBC) profiles, and extract levees by a novel automatic approach.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Fagan and Nanson (2004) found that channels occur over 83% of the Cooper Creek floodplain. Also, with the increased availability of high‐resolution lidar data channel networks from smaller floodplains have been assessed in agricultural (David et al., 2017) and in densely forested (Xu et al., 2020) locations. Hence, channel networks appear to be characteristic features of floodplains across many environments and spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…The densely forested study site is 18.8 km long, and up to 5.9 km wide with a total area of 93 km 2 . Mean floodplain valley elevation declines from 35.0 to 24.5 m giving an average valley gradient of 4 × 10 −4 (Xu et al., 2020). The floodplain is bound by the Congaree River to the south and southwest and by bluffs to the north (Figure 1a).…”
Section: Study Region and Hydrologic Conditionsmentioning
confidence: 99%
“…The main channel along the CNP boundary is 39.1 km long with a gradient of 1.5 × 10 −4 . Xu et al (2020) showed that the bank elevation profile has a highly variable levee/bank crest height, thereby facilitating irregular along-channel inundation patterns. In particular, the levees in the upstream reach require a higher river stage for overbank inundation and therefore favor through-bank inundation, while in the downstream reach, the levees are lower and overbank inundation occurs at lower river stages (Xu et al, 2020).…”
Section: Study Region and Hydrologic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation